Glucose Biosensor Using Selected Indonesian Bacteria - DYAH ISWANTINI; NOVIK NOVIK; . TRIVADILA (Microbiology Indonesia, 2011)
Microbial glucose sensors have been developed using Escherichia coli bacterial strains from Japan. However, there is interest in developing local bacteria as glucose sensors in Indonesia. In this research, the stability and the potential of a selected number of Indonesian bacteria as glucose biosensors was explored. Results of this study indicate that three of them, E. coli, Bacillus subtilis, and Thermus filiformis exhibit properties of high viability and stability at high temperature (30-60 ºC). Spectrophotometrical and electrochemical measurements showed significant absorbance values and highly stable current features for E. coli as indicated by its high capacity to produce glucose dehydrogenase. E. coli, B. subtilis, and T. filiformis produced currents of 3.25 µA, 0.2 µA, and 0.02 µA respectively, and E. coli also produced a much higher activity of glucose dehydrogenase. Electrochemical measurement using E. coli-modified carbon paste electrode allowed the determination of glucose concentration of up to 20 mM. Therefore, Indonesian E. coli has a high stability and can be used as a glucose biosensor